Myositis ossificans on the forearm in a 10-year-old girl - Say, Ferhat; Coşkun, Sina; Bülbül, Murat; Alıcı, Ömer (Lippincott Williams and Wilkins, 2015)
Myositis ossificans is a rarely encountered benign lesion characterized by a non-neoplastic heterotopic bone formation in both soft tissue and skeletal muscle. Three subgroups of myositis ossificans are identified: myositis ossificans progressiva, which is hereditary; nontraumatic or pseudomalignant myositis ossificans, which is developed in the absence of any trauma; and myositis ossificans circumscripta, which is related to evident and direct trauma. In this case report, we present a girl with a swelling on the forearm who was finally diagnosed with nontraumatic myositis ossificans.
WOS: 000352078400009
PubMed ID: 25647566
Keywords: Child; Forearm; Mass; Myositis Ossificans